Knowledge, attitude, practice, and determinants emergency contraceptive use among women seeking abortion services in Dire Dawa, Ethiopia. - Meskerem Abate (Public Library of Science (PLoS), 2014)
Background Unplanned pregnancy from casual sex, unplanned sexual activity, and sexual violence are increasing. Emergency Contraceptives (EC) are used to prevent unplanned pregnancies thereby preventing the occurrence and consequences of unplanned pregnancy. Emergency contraception is widely available in Ethiopia particularly in major cities. Yet the use of EC is very low and abortion rate in cities is high compared to the national average. Objectives To assess knowledge, attitude and practice and determinants on the use of emergency contraception among women obtaining abortion service at selected health institutions in Dire Dawa, Eastern Ethiopia. Methods A facility based cross-sectional study was conducted on 390 women selected by multi-stage random sampling technique. The samples were generated from government and private for non profit health facilities. Participant's knowledge and attitude towards emergency contraception were measured using composite index based on 7 and 9 questions, respectively and analyzed using mean score to classify them as knowledgeable or not, and have positive attitude or not. Practice was assessed if the women reported ever use of emergency contraception. Determinants of use of emergency contraception were analyzed using logistic regression. Result Out of 390 women interviewed, 162 women (41.5%) heard about EC, only 133 (34.1%) had good knowledge, and 200 (51.3%) of the respondents had positive attitudes towards to EC. Ever use of EC was reported by 38 (9.7%). Age, living arrangement, education, marital status, religion were found to be significantly associated with the use of emergency contraceptives. Women with poor knowledge were less likely to use EC compared to the knowledgeable ones [AOR = 0.027, 95% CI (0.007, 0.105)]. Conclusion The study identified that most respondents lack adequate knowledge on the method of EC. In addition ever use of EC is very low. Recommendations Health professions should give attention in increasing knowledge and uptake of Emergency Contraception.